In vitro Inoculation of Fresh or Frozen Rumen Fluid Distinguishes Contrasting Microbial Communities and Fermentation Induced by Increasing Forage to Concentrate Ratio - Ma, Zhi Yuan; Zhou, Ju Wang; Yi, Si Yu; Wang, Min; Tan, Zhi Liang (Frontiers in Nutrition, 2022)
In vitro rumen batch culture is a technology to simulate rumen fermentation by inoculating microorganisms from rumen fluids. Although inocula (INO) are always derived from fresh rumen fluids, frozen rumen fluids are also employed for the advantages of storing, transporting, and preserving rumen microorganisms. As frozen INO can alter the fermentation mode, which may be interacted incubated types of substrates. The present study was designed to test whether rumen fluid treatment (i.e. fresh and frozen) could interact with incubated substrates. A complete block design with fractional arrangement treatment was used to investigate the effects of INO (fresh or frozen rumen fluids) and concentrate to forage ratios (C/F, 2:8 or 5:5) on rumen fermentation and microbial community. The effects of increasing C/F were typical, such as increased substrate degradation and VFA concentration (P < 0.001), and decreased acetate to propionate ratio (P = 0.01) and bacterial diversity of richness and evenness (P ≤ 0.005) with especially higher fermentative bacteria such as Rikenellaceae_RC, F082, Prevotella, Bacteroidales_BS11, Muribaculaceaege, and Christensenellaceae_R-7 (P ≤ 0.04). Although frozen INO had lower (P < 0.001) substrate degradation and altered rumen fermentation with decreased (P < 0.001) acetate to propionate ratio than fresh INO, typical effects of C/F were independent of INO, as indicated by insignificant INO×C/F interaction on substrate degradation, VFA profile and bacterial community (P ≥ 0.20). In summary, we firstly report that effect of C/F on fermentation and bacterial diversity is not interfered by INO mode, and preserved frozen INO can be used to distinguish effect of starch content.